The education gospel : the economic power of schooling - Grubb, W. Norton (Harvard University Press, 2004)
Annotation In this hard-hitting history of "the gospel of education," W. Norton Grubb and Marvin Lazerson reveal the allure, and the fallacy, of the longstanding American faith that more schooling for more people is the remedy for all our social and economic problems--and that the central purpose of education is workplace preparation. But do increasing levels of education accurately represent the demands of today's jobs? Grubb and Lazerson argue that the abilities developed in schools and universities and the competencies required in work are often mismatched--since many Americans are under-educated for serious work while at least a third are over-educated for the jobs they hold. The ongoing race for personal advancement and the focus on worker preparation have squeezed out civic education and learning for its own sake. Paradoxically, the focus on schooling as a mechanism of equity has reinforced social inequality. The challenge now, the authors show, is to create environments for learning that incorporate both economic and civic goals, and to prevent the further descent of education into a preoccupation with narrow work skills and empty credentials